1999
DOI: 10.1111/j.1745-4557.1999.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical, Flavor and Sensory Characteristics of Two Sweet Cherry Varieties Grown in ‘Valle Del Jerte’ (Spain)

Abstract: Volatile compounh and physical, chemical and sensory characteristics of two sweet cherry varieties autochthonous from 'Valle del Jerte I, in the Southwest of Spain, during I995 and 1996 seasons were investigated. 'Pic0 Colorado' had higher values of lightness, chroma, hue, firmness and Braacid ratio than 'To whom correspondence should be addressed. Phone and fax: 34-924-272204. Journal of Food Qualify 22 (1999) 403-416. All Riglvs Resewed. Topyriglv I999 by Food & Nurition Press, Inc. ~ Trumbull, Connecticut 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
47
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 9 publications
10
47
2
Order By: Relevance
“…in our study the ph value was between 3.79 (cScS7, blackish colored) and 4.18 (cScS19, red colored) which is in agreement with the investigations of Bernalte et al (6) in which 2 sweet cherry cultivars originating from Spain were analyzed. our data are also in accordance with the results of hepaksoy et al (16) who analyzed 4 sweet cherry cultivars originating from turkey, europe and USA, Kuden et al (20) who analyzed 21 sweet cherry cultivars from turkey, USA and europe and Vursavus et al (39) who used 3 sweet cherry cultivars from turkey, USA and France.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…in our study the ph value was between 3.79 (cScS7, blackish colored) and 4.18 (cScS19, red colored) which is in agreement with the investigations of Bernalte et al (6) in which 2 sweet cherry cultivars originating from Spain were analyzed. our data are also in accordance with the results of hepaksoy et al (16) who analyzed 4 sweet cherry cultivars originating from turkey, europe and USA, Kuden et al (20) who analyzed 21 sweet cherry cultivars from turkey, USA and europe and Vursavus et al (39) who used 3 sweet cherry cultivars from turkey, USA and France.…”
Section: Resultssupporting
confidence: 93%
“…the results for total phenolics clearly showed that there were wide differences among blackish, dark red, red and yellow skin colored wild sweet cherry fruits. earlier, total phenolic content in sweet cherry fruits was reported from 23-264 mg GAe/100 g fresh weight (6,12,13,38) indicating that plant genotype strongly affects total phenolic content in sweet cherries. it is well-known that phenolic compounds contribute to fruit quality and nutritional value in terms of modifying color, taste, aroma and flavor, and also in providing health-beneficial effects (35).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Sweetness is mainly due to glucose and fructose and lower presence of sucrose and sorbitol, with a range of total soluble solids (TSS) of 11-20 8Brix, depending on cultivar. Acidity (TA) depends also on cultivar, with levels of 0.4-1.5%, the main organic acid being malic acid (Bernalte, Hernández, Vidal-Aragó n, & Sabio, 1999;Bernalte, Sabio, Hernández, & Gervasini, 2003;Esti, Cinquanta, Sinesio, Moneta, & Di Matteo, 2002). Fruit firmness is also an important quality attribute and is directly related to enhance the storability potential and to induce greater resistance to decay and mechanical damage (Barret & González, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Sweet cherries have a higher tolerance to elevated CO 2 concentrations than most stone fruit crops (Tian et al 2001(Tian et al , 2004Petracek et al 2002). Th e impact of controlled atmosphere storage (CA) on the production of volatile compounds by sweet cherry fruits was studied by analysing the compounds released from fruit into the ambient atmosphere (Mattheis et al 1991;Meheriuk et al 1995;Bernalte et al 1999;Goliáš et al 2010). Dynamic headspace gas chromatogramy (GC) methods show that the pre-dominant fl avour volatiles are (E)-2-hexenol, benzaldehyde, hexanal and (E)-2-hexenal, but some compounds observed after 4 weeks of storage appeared to be unrelated to the storage conditions and may refl ect metabolic changes which occur during fruit senescence.…”
mentioning
confidence: 99%